Analysis of Building Construction Project Management Using Lean Construction Approach to Determine Cost and Time Waste in the Construction Project of Pondok Pesantren Syifaul Qulub Surabaya - Efendi, Muhammad; Tjendani, Hanie Teki; Wulandari, Esti (International Journal Labs, 2025)
This research investigates cost waste in detailed engineering design for the Syifaul Qulub Surabaya Islamic Boarding School construction project, aiming for on-time, on-budget completion. Utilizing a Lean Construction approach, the study analyzes waste reduction in this densely populated, limited-access urban environment. Primary data from questionnaires were processed to weigh waste in each activity, followed by value stream analysis tools, including Process Activity Mapping, to identify Value-Added (VA) and Non-Value-Added (NVA) activities. The findings revealed that waiting was the primary cause of waste, contributing to 41.8% of critical waste and a 33-day project delay. Root causes included material procurement issues, transportation challenges, and equipment problems. Waste accounted for 21% of all project jobs, categorized as Unnecessary Movement (13.7%), Transportation (12.2%), Material Defects (11%), Storage (10.9%), and Overproduction (6.8%). By addressing these wastes through targeted Lean interventions, the research suggests a potential project acceleration of approximately 16.5% (33 days) and a cost reduction of 5-10% by optimizing resource use and minimizing material waste. These results demonstrate the practical benefits of Lean Construction in mitigating inefficiencies and delays in challenging urban builds.